2023
DOI: 10.1177/10711007231217273
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Operative Correction of Equinus in Cerebral Palsy on Gait Patterns

Axel Horsch,
Lara Petzinger,
Julian Deisenhofer
et al.

Abstract: Background: This study aimed to evaluate gait outcomes and strength following the surgical correction of equinus in cerebral palsy (CP) based on different surgical procedures. We included the Baumann and Strayer procedures, as well as the Achilles tendon lengthening (ATL). Methods: A retrospective analysis was performed in patients with infantile, bilateral CP who received instrumental 3D gait analysis before and after surgical correction (18.66 months postoperatively). Patients were divided into 3 groups: Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Horsch evaluated gait outcomes and strength following different surgical procedures of the equinus foot in two groups of patients with CP and found that the Strayer procedure and Achilles tendon lengthening showed higher postoperative dorsiflexion. Moreover, an 8.2% loss in calf muscle strength was observed in the Strayer group, while in the Baumann procedure, no loss of strength was observed, and maximum power improved postoperatively ( 62 ). The hip is the second most commonly affected joint in patients with CP, thus hip surveillance programs are recommended to prevent, reduce, and identify hip dislocation ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Horsch evaluated gait outcomes and strength following different surgical procedures of the equinus foot in two groups of patients with CP and found that the Strayer procedure and Achilles tendon lengthening showed higher postoperative dorsiflexion. Moreover, an 8.2% loss in calf muscle strength was observed in the Strayer group, while in the Baumann procedure, no loss of strength was observed, and maximum power improved postoperatively ( 62 ). The hip is the second most commonly affected joint in patients with CP, thus hip surveillance programs are recommended to prevent, reduce, and identify hip dislocation ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, several studies explored the impact of surgical treatment on some speci c outcomes. Horsch et al 22 explored the impact of operative correction of equinus in CMT on gait patterns. They showed that Baumann surgery pes equinus treatment could signi cantly improve the gait of children and adults with cerebral palsy.…”
Section: Discussionmentioning
confidence: 99%